Innovations in clothing technology & measurement techniques - (:unkn) unknown (Wydawnictwo Politechniki Łódzkiej, 2012)
[...]It is worth to point out that the monograph "Innovations in Clothing Technology and Measurement Techniques" covers almost all the stages of clothing and footwear production starting from the scanning the human body, through the innovative mass customization technology of clothing production, automatic sewing process, clothing textronics solutions, measurement techniques in the clothing industry, finishing on the problems dealt with clothing appearance, fashion and design. It should be mentioned that the clothing industry is very innovative, still developing and a promising sector in the European economy. Also in our country the clothing industry gathers many small and medium enterprises, which have good development perspectives for the future. The monograph consists of four chapters titled as follows: 1. Clothing and Footwear- Construction and Computer Techniques, 2. Smart textiles and Wearable Electronics, 3. Innovations in Measurement Techniques, 4. Fashion and Clothing Design. The chapter titled Clothing and Footwear - Construction and Computer Techniques is the longest one due to the fact that all the problems dealing with the preparation of technological clothing production are very actual now, especially in the European countries. Scanning technology opens the new possibilities for creating the clothing patterns. Using the scanning technique and appropriate software we are able to adjust the clothing to fit better to the human being silhouette. The topics concerned so called "smart textiles" are also very modern now. It is caused by the need of changing the clothing functionality. In addition to cover the human body the clothing can fulfill the other functions like heating, warning the person about any dangerous situations, for example, to warn the fire-fighter, who is involved in the action, that he should leave the dangerous territory. The textronics applied in the clothing can also fulfill the functions important for the health of the user, for example, it can measure the human physiological parameters. The textronics can be also used in the PPE, can enable the specially important data transmission. Shortly speaking this is the content of the next chapter - Smart Textiles and Wearable Electronics. In the chapter Innovations in Measurement Techniques there are described methods used in the clothing physiological comfort measurement (microclimate parameters and water vapor permeability), methods for testing the relaxation properties in the multilayer textile materials, color change of textile materials by a new device DigiEye as well as methods of assessment of special properties important from the safety point of view like a flammability. The chapter Fashion and Clothing Design is devoted for the clothing art designing also with the use of new tools like CAD. The Authors are trying to explore the impact of using the Virtual Reality Technology in fashion communication advertising as a medium, which can be used in fashion photo sessions, fashion shows and fashion shops to improve the acceptance of information on the market. Fashion advertising is a main branch, which focuses on a promotion of the fashion industry. This monographic edition is prepared by many Authors from different countries like: Germany, Slovenia, Ukraine, Russia, Portugal, Lithuania, Belgium, Slovakia, Egypt and Poland. Some of the presentations are prepared in the international cooperation. I would like to thank all the Authors for an effort they undertook to contribute this monograph. Dear Friends, thanks a lot for your very interesting contributions, which make the monograph very consistent and valuable.
Partnerzy konferencji : 1. Central Institute for Labour Protection - National Research Institute 2. Technical University of Lodz, Department of Clothing Technology and Textronics 3. Kazimierz Pułaski Technical University of Radom. Departmemnt of Design, Footwear and Clothing Technology
Red. nauk. Wydziału : Kowalski, Krzysztof
Red. serii : Wodziński, Piotr
The monograph contains publications submitted to the 10 th Joint International Scientific Conference CLOTECH 2012 on 'Innovative materials & technologies in made-up textile articles, protective clothing and footwear'
Keywords: ubiory - projektowanie i konstrukcja - konferencje; obuwie - projektowanie i konstrukcja - konferencje; ubiory ochronne - konferencje; tkaniny i tekstylia - innowacje - konferencje; ubiory - design - konferencje; clothing - design and construction - conferences; footwear - design and construction - conferences; protective clothing - conferences; fabrics and textiles - innovations - conferences; clothes - design - conferences